2019
DOI: 10.1038/s41598-019-53717-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Genes between Carrot Petaloid Cytoplasmic Male Sterile and Maintainer during Floral Development

Abstract: Petaloid cytoplasmic male sterility (CMS) is a maternally inherited loss of male fertility due to the complete conversion of stamens into petal-like organs, and CMS lines have been widely utilized in carrot breeding. Petaloid CMS is an ideal model not only for studying the mitochondrial–nuclear interaction but also for discovering genes that are essential for floral organ development. To investigate the comprehensive mechanism of CMS and homeotic organ alternation during carrot flower development, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
10
1
Order By: Relevance
“…The mitochondrial transcriptomes exhibited only very few differences in coverage or editing between F and H [ 12 , 24 ], the plastid transcriptomes were completely identical between F and H [ 25 ]. Our observations contradict some studies, e.g., [ 19 ], which described numerous mitochondrial DE genes between male sterile and male fertile individuals. This discrepancy may be sometimes explained by experimental artifacts.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The mitochondrial transcriptomes exhibited only very few differences in coverage or editing between F and H [ 12 , 24 ], the plastid transcriptomes were completely identical between F and H [ 25 ]. Our observations contradict some studies, e.g., [ 19 ], which described numerous mitochondrial DE genes between male sterile and male fertile individuals. This discrepancy may be sometimes explained by experimental artifacts.…”
Section: Resultscontrasting
confidence: 99%
“…We observed the inhibition of several genes related to fatty acid synthesis, wax and cutin formation in S. vulgaris females (two transcripts coding for pectinesterases (DN44106_c0_g1, DN69711_c0_g1), the transcript for UDP-arabinopyranose mutase (DN59301_c0_g4) involved in cell wall modifications [ 52 ]). Genes with similar functions were also inhibited in male sterile individuals e.g., in radish and other crops [ 14 , 15 , 16 , 17 , 18 , 19 , 53 ]. In contrast, the transcripts coding for catabolic enzymes lipases and esterase (DN57332_c1_g2, DN61032_c0_g1), or caleosin (DN54044_c1_g1), functioning in degradation of storage lipids, were upregulated in females ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…KEGG pathway analysis showed that many DEGs were involved in secondary metabolite biosynthesis, including carbon metabolism, ribosome, protein processing in the endoplasmic reticulum and amino acid biosynthesis. Furthermore, plant oxidative phosphorylation that plays an important role in plant floral development ( Liu et al, 2019 ) is also activated.…”
Section: Discussionmentioning
confidence: 99%